Konstruksi Asbābun Nuzūl M. Abed Al-Jabiri (Studi Kitab Fahm Al-Qur’ān Al-Hakīm: Al-TafsīrAl- Wadhih Hasb Al-Nuzūl) - M. Mansur Abdul Haq; Munawir Munawir (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
Asbābun nuzūl is an important element in the interpretation treasures of the Qur'an, especially contemporary interpretations that emphasize the relevance of the times with a comprehensive study of the socio-historical context (al-siyāq al-tārīkhi al-ijtimā’i) which covers the revelation process of the Qur'an. In this regard, various contributions have been made by contemporary Islamic thinkers. This paper examines one of the contemporary Islamic thinkers, M. Abed al-Jabiri, with his commentary Fahm al-Qur’ān al-Hakīm: al-Tafsīr al-Wadhih Hasb al-Nuzūl. Unlike the interpretation in general, the book is compiled based on tartīb nuzūli. Namely, arranged in the order the Qur'an was revealed. The construction of asbābun nuzūl offered by al-Jabiri is different from asbābun nuzūl in general, and has an important role in the book of interpretation. With the theoretical framework of Karl Mannheim's sociology of knowledge, descriptive-analytical methods, and historical-philosophical approaches, the writer finds that asbābun nuzūl in al-Jabiri's conception is not sufficiently based on the shahih history of asbābun nuzūl (micro), and also on its suitability with the social, economic, intellectual, and Arab civilization conditions (macro),but also must be based on its suitability with the narrative/content logic of the verse that is based on the asbābun nuzūl.